Optimization of the Minmax Function as Inventory Management on Non-Prescription Products at Kimia Farma Pharmacy Balikpapan - Fatroni, Hanif; Saragi, Sahat; Widyastuti, Sri (International Journal of Science and Society, 2024)
The minmax method is the method applied by Kimia Farma Pharmacy Balikpapan. There are some constraints in this method, such as empty stock, impact on turnover, and visits. The purpose of this research is to see the effect of optimization of minmax method on inventory management that affects customer satisfaction, increase in turnover and number of visits. The research method used descriptive quantitative One Group Design Pre and Post Test method and cross-sectional analytical survey. Researchers observed the variables of customer satisfaction, non-prescription turnover and visits before and after the minmax method intervention, looking at the correlation between customer satisfaction and the increase in turnover and visits. A survey was conducted with 379 customers before and after the intervention to see customer satisfaction. Optimization of the minmax method after the intervention, namely orders via defect with a frequency of every day, cito orders, adding SKU (Stock Keeping Unit) items, HR control of goods. The results of the study before the intervention were Pareto A availability of 81.2%, SKU 2453, and inventory life of 66 days. The customer satisfaction index is 3.38, the average non-prescription and visit turnover is Rp. 811,753,502 and 7818, while after the intervention the increase in pareto A availability is 95.8%, SKU 3346, and inventory life is 42 days. The customer satisfaction index is 4.61, the average non-prescription turnover and visits are Rp. 1,140,740,604 and 9940. Optimization of minmax method is successfully applied by Kimia Farma Pharmacy Balikpapan and has an influence on customer satisfaction, turnover, and visits.